A taxisblokád és utóélete - Kihívás a társadalomtudományok számára - Szabó, Máté (Szociológiai Szemle, 2024)
The treatise sums up the results of the debates, held at the 1992 autum conference of the Hungarian Sociological Society, in the section having the same title. The taxi drivers’ blockade was analysed from the point of view of the underlying causes, its dynamics, the organizational form, the forms of its actions, the social and political framework, primarily the political and administrative control and the reactions of the political control system. From a theoretical-methodological standpoint various approaches are applied in the analysis of the taxi drivers’ blockade: the sociological intervention, the logic of rational behaviour, the approach of cultural anthropology, that of communicative discourse and also the evaluation of the reactitons of the political parties and interest-organizations, together with the analysis of the social movements. As a conclusion it was stressed that the taxi drivers’ blockade highlighted a serious problem of the post-Socialist societes, the threats of mass actions, deriving from the social problems of the transition to the market economy — threats which directly questioned the stability of the newly established democratic political order.